The Fluid Dynamics of Climate - Provenzale, Antonello; Palazzi, Elisa; Fraedrich, Klaus (CISM International Centre for Mechanical Sciences, Courses and Lectures, 2016)
This volume provides an overview of the fluid aspects of the climate system, focusing on basic aspects as well as recent research developments. It will bring together contributions from diverse fields of the physical, mathematical and engineering sciences. The volume will be useful to doctorate students, postdocs and researchers working on different aspects of atmospheric, oceanic and environmental fluid dynamics. It will also be of interest to researchers interested in quantitatively understanding how fluid dynamics can be applied to the climate system, and to climate scientists willing to gain a deeper insight into the fluid mechanics underlying climate processes.